What Explains the Duration of Unemployment among the Educated First Job Seekers in the Republic of Congo? - Henri Bello Fika (Yayasan Riset dan Pengembangan Intelektual, 2023)
The aim of this paper is to identify the determinants of the duration of unemployment among the educated first job seekers in the Republic of Congo. To achieve this goal, we make use of data which have been constructed from the database of the School-to-Work Transition Survey (SWTS) carried out in Congo in 2015 by Iinternational Labor Organization (ILO) among people who are between 15 and 29 years old. The sample formed for our study is made up of people who have at least a primary educational level, who have been employed at least once in their life and who have stopped study or training before getting their first job. The sample is made up of 1,171 individuals including 565 males and 606 females. Using these data, we perform a descriptive statistical analysis supplemented by an explanatory analysis based on the Poisson regression model. The explanatory variables we choose are: the educational and qualification level, the area of training, gender, age and the type of employment. Our main finding is that the trainig area and level are important factors of the school-to-first-job transition. This transition is shorter for people who have a background in the fields of applied sciences (Production and Process Engineering, Maths and Computer Science, Medicine, Agriculture, Managementbusiness,...). Hence, the point is not only to increase the human capital stock, but also to form a human capital structure that corresponds to the real needs of the economy, so that the duration of the transition between the cessation of studies or training and access to the first job is considerably reduced.